Associations between COVID-19 infection and sex steroid hormones - Cai, Zixin; Zhong, Jiaxin; Jiang, Yingling; Zhang, Jingjing (Frontiers in Endocrinology, 2022)
Aims: Coronavirus disease 2019 (COVID-19) is caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and within a few months of the first outbreak, it was declared a global pandemic by the WHO. The lethal virus SARS-CoV-2 is transmitted through respiratory droplets and enters host cells through angiotensin-converting enzyme 2 (ACE-2) receptors. ACE-2 receptors are highly expressed in many tissues, including testes. Therefore, the objective of this study is to summarize the available literature regarding the correlation between sex hormone levels and COVID-19. Methods: The PubMed, Web of Science, Embase, and Cochrane Library databases were reviewed systematically through April 2022 for studies comparing sex hormone levels between different patient groups: COVID-19 versus no COVID-19, more severe versus less severe COVID-19, and nonsurvivors versus survivors. Various types of clinical research reporting sex hormone levels, including total testosterone (TT), luteinizing hormone (LH), follicle-stimulating hormone (FSH), 17β-oestradiol (E2), the oestradiol-to-testosterone ratio (E2/T), prolactin (PRL), and sex hormone-binding globulin (SHBG), were included. Random- or fixed-effects models were used to calculate the weighted mean differences (WMDs) and 95% confidence intervals (CIs). Results: Twenty-two articles that included 3369 patients were finally included in the meta-analysis. From the analysis of the included studies, patients with COVID-19 had a significantly lower TT, T/LH, FSH/LH, and SHBG levels and high levels of FSH, LH, and E2/T, but their levels of PRL, E2, and progesterone were not affected. Publication bias was not found in our analysis according to the funnel plot, Egger’s regression and Begg’s rank correlation tests. Conclusion: Low TT, T/LH, FSH/LH, and SHBG serum levels and high FSH, LH, and E2/T levels may increase the risk of COVID-19. On the other hand, the greater the clinical severity of COVID-19 is, the higher the probability of increases in FSH, LH, and E2/T serum levels and decreases in the levels of TT, T/LH, FSH/LH, and SHBG. COVID-19 may have unfavourable effects on gonadal functions, which should be taken seriously by clinicians. Routine monitoring of sex hormone levels might help clinicians evaluate disease severity in patients with COVID-19.